ALMA View of the High-velocity-dispersion Compact Cloud CO 0.02–0.02 at the Galactic Center - Yuhei Iwata; Tomoharu Oka; Shunya Takekawa; Shiho Tsujimoto; Rei Enokiya (The Astrophysical Journal, 2023)
We report the results of observations toward the center of the molecular cloud CO 0.02–0.02 made using the Atacama Large Millimeter/Submillimeter Array. The successfully obtained 1″ resolution images of CO J = 3–2, H ^13 CN J = 4–3, H ^13 CO ^+ J = 4–3, SiO J = 8–7, CH _3 OH J ${}_{{\text{}}{K}_{a},K_{c}}$ = 7 _1,7 –6 _1,6 A ^+ lines, and 900 μ m continuum show several new features, which have not been identified in previous observations. The dense gas probe (H ^13 CN, SiO, CH _3 OH) images are dominated by a pair of northeast-southwest elongated filaments, which may be the main body of CO 0.02–0.02. Two striped patterns perpendicular to each other (F1 and F2) and a high-velocity feature (HV), which appear in different velocity ranges, were prominent in the CO image. An emission hole that may represent an expanding feature was found in the F1 velocity range. F2 appeared to align along the western edge of a 20 pc × 13 pc ellipse (the Large Shell) identified in the single-dish CO map. The HV contains eight compact clumps at the positive high-velocity end of the CO emissions. Based on these results, we propose a formation scenario for CO 0.02–0.02; internal explosions of supernovae, external perturbations by the Large Shell, and gravitational acceleration by a less-luminous star cluster have formed CO 0.02–0.02 in its current state.